Texting while walking: An expensive switch cost - Courtemanche, Francois; Labonté-LeMoyne, Elise; Léger, Pierre-Majorique; Fredette, Marc; Senecal, Sylvain; Cameron, Ann-Frances; Faubert, Jocelyn; Bellavance, Francois (Accident analysis and prevention, 2019)
•This study investigates the cognitive and attentional processes underlying switch cost during texting while walking.•Participants had to discriminate the orientation of an oncoming human shape.•Participants who were texting while walking performed significantly worse than those who were only walking.•Using EEG and behavioral data, this study provides an initial understanding of how texting while walking impacts pedestrians.•This may indicate that the more inhibition is needed, the more the performance is affected by texting. Texting while walking has been highlighted as a dangerous behavior that leads to impaired judgment and accidents. This impairment could be due to task switching which involves activation of the present task and the inhibition of the previous task. However, the relative contributions of these processes and their brain activity have not yet been studied. We addressed this gap by asking participants to discriminate the orientation of an oncoming human shape in a virtual environment while they were: i) walking on a treadmill, or ii) texting while walking on a treadmill. Participants’ performance (i.e., correctly identifying if a walker would pass them to their left or right) and electroencephalography (EEG) data was collected. Unsurprisingly, we found that participants performed better while they were only walking than when texting while walking. However, we also found that the diminished performance is differently related to task set inhibition and task set activation in the two conditions. The alpha oscillations, which can be used as an index of task inhibition, have a significantly different relation to performance in the two conditions, the relation being negative when subjects are texting. This may indicate that the more inhibition is needed, the more the performance is affected by texting. To our knowledge, this is the first study to investigate the brain signature of task switching in texting while walking. This finding is the first step in identifying the source of impaired judgment in texting pedestrians and in finding viable solutions to reduce the risks.